0792 SLEEP OPTIMIZATION IMPROVES MOOD DIFFERENTLY BETWEEN CANADIAN NATIONAL TEAM CURLERS AND ROWERS. (28th April 2017) - Bender, AM; Werthner, P; Samuels, CH
Abstract: Introduction: Elite athletes are at-risk for insufficient sleep, but research on sleep interventions in this population is limited. The current study utilized three different sleep optimization interventions with curlers and female heavyweight rowers to see if optimal sleep would affect mood states differently. Methods: N=15 Canadian National Team curlers (mean age 30.7 ± 4.5; 8 females) and 11 Canadian Women's heavy-weight National Team rowers (mean age 26.0 ± 3.1) completed the Profile of Mood States at two time points during their competitive season; once before the sleep interventions (baseline; BL), and once after the 3.5-week sleep intervention (SI) phase. The sleep interventions consisted of increasing nighttime sleep, napping, and reducing the negative effects of technology use by putting away electronic devices an hour before bedtime. All interventions were the same between sports except the rowers additionally wore blue-blocking glasses in the two hours before bedtime. Data were analyzed with independent samples t-tests to compare differences in POMS sub-scales of tension-anxiety, depression, fatigue, vigor, and total scores between both sports at baseline. Paired sample t-tests by sport were used to compare changes in the sub-scales and total mood scores between baseline and post-intervention. Results: At BL, the rowers had higher levels of tension-anxiety (t24 =2.51, p=0.019), fatigue (t24 =2.90, p=0.008), depression (t24 =2.18, p=0.039), and total mood symptoms (t24 =2.14, p=0.043) when compared to the curlers. The rowers reduced depression symptoms after the SI phase (t10 =2.84, p = 0.018). The curlers reduced fatigue (t14 =2.63, p=0.020), increased vigor (t14 =2.97, p=0.010), and reduced total mood symptoms (t14 =2.70, p=0.017) after the SI phase. Conclusion: In this sample of elite athletes from two different National Team sports, the rowers had poorer mood symptoms at BL and did not improve mood states as much as the curlers after the SI phase. It is likely that stress related to the preparations for the Rio 2016 Summer Olympics hindered the effectiveness of the interventions in the rowers. Further research is needed to assess the interventions across the Olympic quadrennial preparation cycle and to determine the optimal implementation strategy for different teams and athletes. Support (If Any): Own the Podium and Mitacs Accelerate.